The Model of Youth Development Based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project - Wipatasinlapin, Naetchanok (Journal of International Buddhist Studies, 2017)
The objectives of this research are 1) To study the youth development status based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project 2) To develop the model of youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project 3) To propose the model of youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project in the Participatory Action Research. The Quantitative Research consists of 1) The In-Depth Interview of 45 monks/laymen by analyzing the overall data 2) Seminar of 10 important informants who are monks and laymen. The data analysis is carried out by analyzing the content and concluding the seminar results and 3) Group conversation for five monks/laymen who are important informants. The data analysis is carried out by analyzing the content and concluding the group conversation results. The research results found that For the status of youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project, we found that the process in youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project such as 1) Ideas include learn – play – be – change 2) The goals are changing yourself and changing people in the whole world. 3) The curriculum is youth development based on the Threefold Training Principles which are Precept, Meditation and Intelligence. We have developed the youth according to the Threefold Training Principles throughout 4 weeks. Topics include 1) Learning in Dhamma and Doing in the World. The second topic is Play – Playing Well and Developing Intelligence. The 3rd topic is Be which is Be the Best at Your Standpoint. And the fourth topic is Change Yourself to the New One. From the model of youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project, we found that the youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project under the theme “loving, waiting, contentment, giving” consist of 4 procedures which are 1) Preparation of project management plans 2) Implementation of main components 3) Youth development based on the Threefold Training Principles 4) Youth follow-up and development 5) Project management improvement and development and 6) Project management evaluation and communication plans. The youth development based on the Threefold Training Principles in Samanera Plookpanya Dhamma Project is the use of novice monkhood in summer for further communication. It is the broadcast of these young novices ordination for 4 weeks. They need to be trained and comply with training rules as well as study the Buddhism principles through the historical background of the Lord Buddha. Moreover, there are a wide variety of learning from master monks and lecturers under the theme “Learn to Love with Dhamma Principles, Learn to Wait without Discouragement, Learn to be Content for Happiness and Learn to Give for Happy Mind”. The use of Threefold Training Principles that consist of precept, meditation and intelligence is the processes in training and developing youth to have the positive behavior in accordance with 3 perspectives of the Threefold Training Principles. They are 1) Self-development in precept 2) Self-development in meditation 3) Self-development in intelligence. They can develop these 3 important perspectives when they are ordained and will be able to adapt them in their daily lives after they leave the Buddhist monkhood.